PENGARUH PROMOSI DAN FLASH SALE TERHADAP PERILAKU IMPULSIVE BUYING PADA PENGGUNA E-COMMERCE: Survei pada Mahasiswa FKIP Unpas Angkatan 2021 Semester Genap Tahun Ajaran 2024/2025 - Isela Hidayah; Ani Setiani; Yudho Ramafrizal S. (Universitas Pasundan, 2025)
This research aims to find out: (i) How much influence of promotion on impulsive buying behavior among students who use e-commerce at FKIP Unpas; (ii) How much influence of flash sales on impulsive buying behavior among students who use e-commerce at FKIP Unpas; (iii) How much influence of promotion and flash sale on impulsive buying behavior among students who use e-commerce at FKIP Unpas. The research method used was a survey using classical assumption test, multiple linear regression, t-test, f test, determination coefficient, and partial determination coefficient. The results of this study show that: (i) There is a significant influence on the Promotion variable (X1) on Impulsive buying (Y) behavior inFKIP Unpas students class of 2021, with a contribution of 47.12%; (ii) There is a significant influence on the Flash Sale (X2) variable on Impulsive buying (Y) behavior in FKIP Unpas students class of 2021, with a contribution of 1.03%; (iii) There was a significant influence of 48.2% on the variables of Promotion (X1) and Flash Sale (X2) on Impulsive buying (Y) behavior in FKIP Unpas students of the class of 2021. The researcher recommends that universities can provide education about digital literacy and personal financial management of students. Students are advised to be more selective and aware in responding to promotions and Flash Sale and manage finances wisely. Further researchers are expected to be able to study this topic more deeply.